A courtly genre in a romantic century: gallant schemes in the guitar minuets of Pedro Ximénez (1784-1856) - Vega Salvatierra, Zoila Elena (2021)
Minuet is a musical genre that received outstanding success both as a dance and as an instrumental genre in the 17th and 18th centuries, and which in turn became a compositional model that exceeded the limits of its own time and was well received by societies that assimilated, restructured and resignified it according to their own realities. The repertoire of minuets for solo guitar, written by Pedro Ximénez Abrill (1785-1856) and published in 1844, is an ideal collection to study the permanence of languages from the previous century in secular spaces such as the musical “salón sudamericano” in the Independence period. Often compared with authors like Fernando Sor or Mauro Giuliani, his contemporary guitarists, Ximénez could be related more closely, musically speaking, to Spanish composers of the previous generation. To support this idea, the first notebook of his Collection of minuets is analyzed, where melodic and nearby accompaniment structures are identified close to the gallant schemes described by Robert Gjerdingen (2014) and which were in vogue in European music in the second half of 18th century.